Realizing impressive superplasticity in a low-alloyed Mg-Zn-Ca-Al-Mn alloy: The roles of grain boundary segregation and dense β-Mn particles - Tian-Shuai Wang; Zhen-Ming Hua; Cheng Wang; Min Zha; Yipeng Gao; Hui-Yuan Wang (Journal of Magnesium and Alloys, 2024)
Achieving impressive superplasticity is an important strategy to manufacture Mg alloy products with complex shapes. In the present study, we report that an excellent superplastic deformation with elongation larger than 500% can be achieved at 623 K and 1.0 × 10−3 s−1 in a Mg-1.51Zn-0.59Ca-0.59Al-0.70Mn (wt.%, ZXAM2111) alloy fabricated by equal-channel angular pressing. The superplastic deformation is mainly carried by grain boundary sliding (GBS), accompanied by a grain size growth from ∼3.0 µm to ∼6.0 µm after deformation. Before deformation, the ZXAM2111 alloy is mainly characterized by a strong co-segregation of Zn and Ca atoms at grain boundaries and uniformly distributed β-Mn particles. With deformation proceeding, the β-Mn particles further dynamically precipitate along grain boundaries that parallel the tensile axis, leading to improved resistance to grain coarsening. Although the enhanced stabilizing effects decrease the strain rate sensitivity value, the resulting impressive microstructure stability provides a cornerstone of the active operation of GBS, facilitating the achievement of superplastic deformation. The present work could provide insight into developing low-alloyed Mg alloys with high microstructure thermal stability to achieve superplasticity.